2020
DOI: 10.26686/wgtn.12469334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale

Abstract: © 2019 John Wiley & Sons Ltd Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large-scale patterns of species richn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This community is among the most diverse scavenger communities described worldwide, with 15 of the 19 of the species detected here being exclusive to the Neotropics (IUCN, 2020;Sebastián-González et al, 2019). We find few scavenging communities with higher species richness in the literature, like the Polish temperate forests, with…”
Section: The Vertebrate Scavenger Assemblage At the Cerrado Biomementioning
confidence: 56%
See 1 more Smart Citation
“…This community is among the most diverse scavenger communities described worldwide, with 15 of the 19 of the species detected here being exclusive to the Neotropics (IUCN, 2020;Sebastián-González et al, 2019). We find few scavenging communities with higher species richness in the literature, like the Polish temperate forests, with…”
Section: The Vertebrate Scavenger Assemblage At the Cerrado Biomementioning
confidence: 56%
“…This is the first time the Cerrado scavenging community is described, and our findings emphasize the importance of the functions and ecosystem services provided by the scavenger guild in this Neotropical region. Several factors have been shown to influence the composition of scavenger communities, such as habitat, topography, and climate (Mateo-Tomás et al, 2017;Sebastián-González et al, 2019Turner et al, 2017). Nevertheless, it has been concluded that human disturbance is the factor that most affects the richness of scavengers (Sebastián-González et al, 2019) and also influences the way scavenger assemblages are structured and their efficiency at the global scale (Sebastián-González et al, 2020).…”
Section: Concluding Remarks and Conservation Implicationsmentioning
confidence: 99%
“…This could be particularly detrimental to long-term plant population resilience when, as we show, some plant species may benefit from the endozoochorous dispersal service provided by facultative scavengers to facilitate recruitment and so completion of their life cycle (Traveset et al, 2012). Our study area had a relatively intact scavenger guild, but anthropogenic pressures are significantly affecting scavenger richness and abundance on a global scale (Sebastián-González et al, 2019. Humans can affect scavenger species directly through persecution (Swenson et al, 1995) but also indirectly through cadaver removal (Margalida et al, 2010), habitat fragmentation and destruction (Sebastián-González et al, 2019).…”
Section: Ta B L Ementioning
confidence: 91%
“…Moreover, the assembly of scavenger guilds (i.e., disperser species) utilizing cadavers (Selva et al, 2005;Turner et al, 2017) and the interactions between a cadaver, scavengers and surrounding habitat may have a considerable impact on whether CDIs, directed dispersal, or seedlings occur. For example, a cadaver deposited in winter might be either completely consumed or scattered over the landscape by scavengers within a relatively short time (Towne, 2000;Turner et al, 2017) Tomás et al, 2017;Sebastián-González et al, 2019. This could be particularly detrimental to long-term plant population resilience when, as we show, some plant species may benefit from the endozoochorous dispersal service provided by facultative scavengers to facilitate recruitment and so completion of their life cycle (Traveset et al, 2012).…”
Section: Ta B L Ementioning
confidence: 95%
See 1 more Smart Citation